Temporal Statistical Analysis and Retrospective Assessment of Mortality Rate in the United States from 1999 to 2018 - , Adedeji Okikiade; , Chidinma Kanu; , Oluwadamilare Iyapo; , Ololade Omitogun; , Richard Adetoye (Archives of Current Research International, 2024)
Objectives: To retrospectively examine the mortality trend in the USA from 1999 to 2018 using a basic statistical model while examining multiple variables. The inferential and descriptive statistical tools will be prioritized to elucidate the mortality of both years in simple terms. Methods: We conducted a retrospective observational descriptive analysis of data on the 10 leading causes of death in the United States by age, race, and sex over 2 decades (1999 to 2018). The data in this report are based on information from all death certificates filed in the 50 states and the District of Columbia. The causes of death are classified by the International Classification of Diseases, 10th Revision (ICD–10), which is ranked according to the number of deaths (Cause-of-death statistics are based on the underlying cause of death). This report supplements “Deaths: Final Data for 2020,” the National Center for Health Statistics’ annual report of final mortality statistics. SPSS (statistical package for social sciences) version 29 Software in Excel sheet was used to analyze the generated datasets. Descriptive and inferential (parametric and non-parametric) analyses were used. The statistically significant relationships and assumptions were made using the chi-square/t-test, Kruskal-Wallis, and Fischer's exact tests with the significance level set at p ≤ 0.05. The analysis and determination of the level of agreement between the initial diagnosis and findings from the new analysis done. Results: The proportion of age-adjusted death rates of the heart (such as coronary artery disease) account for the highest proportion of 24%, while Malignant neoplasms (cancers) represent 23%, Chronic lower respiratory diseases contribute 6%, Unintentional injuries (accidents) also play a significant role, accounting for 5% of deaths. The regression analysis reveals a strong and statistically significant relationship between the number of causes in females and males. There was a high death rate of around 60 years in 1999 and a consistent decline over the years, reaching below 40 by 2018, with a 15/100,000 death fluctuation mark. Asian or Pacific Islander has the lowest age adjustment value of 8762.4, American Indian or Alaska Native, Hispanic, or Latino(11673.2), Black or African American, Hispanic, or Latino (12992.1), White, not Hispanic or Latino(15457.1), Black or African American (15708.2), Hispanic or Latino(19624.1), American Indian or Alaska Native, not Hispanic or Latino (16287.9).Asian or Pacific Islander, not Hispanic or Latino( 8791.3), and 99.2% of the variability in the dependent variable and standard error of 6.7240. Conclusions: Cardiovascular death remains the most common cause of death, with a significant decrease in the death rate from 1999 to 2018 due to improved health care and the provision of measures to improve health care. The regression analysis reveals a strong and statistically significant relationship between the number of causes in females and males. Therefore, based on the results, the number of causes in females strongly predicts the number of causes in males.